Strategi Pembelajaran Edutainment dalam Mata Pelajaran Akidah Akhlak - Wilda Irsyad; Ilpi Zukdi; Muhammad Zalnur (Murabby: Jurnal Pendidikan Islam, 2023)
This research is motivated by a classroom atmosphere that tends to be teacher-centered so that students become passive, the learning process is monotonous which makes learning unpleasant, and then students are bored, and bored in following the learning process. In this case, educators do not apply the principles of Rasulullah's teaching, one of which is to avoid boredom. The purpose of this study was to determine the concept of edutainment strategies and the implementation of edutainment learning strategies in Akidah Akhlak subjects. This type of research is Library research. Data collection techniques through literary data collection, namely by collecting library materials that are continuous (coherent) with the object of discussion under study. Data sources are primary data and secondary data. The data analysis technique that the author uses is data reduction, data presentation, and conclusion-making. Based on the research conducted by the author, it can be concluded that the edutainment strategy in learning is effective enough to be applied and students easily understand the material delivered by educators with this strategy. The implementation of the Edutainment learning strategy that combines education with entertainment in Akidah Akhlak learning can provide a learning process that is very attractive to students' activeness in learning, students feel comfortable, happy, does not cause boredom in the learning process so that the goals set can be achieved properly